PENGARUH KEMUDAHAN PENGGUNAAN, KENYAMANAN AKESTABILITAS, KEAMANAN PENGGUNAAN DAN KEPERCAYAAN PELANGGAN SEBAGAI VARIABEL INTERVENING TERHADAP MINAT BERTRANSAKSI ULANG SECARA E-BANKING (Studi Kasus Pada Nasabah Pengguna Internet Banking di Kota Semarang) - Kharismawan, Ikhsan Toga; Widiyanto, Ibnu (Diponegoro Journal of Management, 2016)
The research aims to determine whether the perceived ease of use, perceived enjoyment access, security and trust to intention to use internet banking, this research aims to analyze the factors most dominant influence on Intention to Use Internet Banking.            The population used in this study is a customer who had used internet banking facilities. The sample in this study of 400 respondents and the techniques used are non-probability sampling technique with accidental sampling approach (sampling by customer who had used internet banking facilities more than doubled to conduct online transactions). The analytical method used was quantitative analysis is multiple regression analysis. This analysis includes: validity and reliability, classic asumtion test, multiple regression analysis, hypothesis testing via test t and test f, the coefficient of determination (R2) and test intervening.